The Practice of Entrepreneurship Education through Extracurricular Activities in Higher Education: Students Perspective - Wudu Melese Tarekegne; Alebachew Hailu Gelaneh (LPPM of NAROTAMA UNIVERSITY, 2019)
Abstract This study was aimed at investigating the practice of entrepreneurship education through extracurricular activities in higher education from students perspective. To achieve this objective descriptive survey research design was used. Data were collected from university students. Accordingly, four universities were selected as sample universities by using simple random sampling technique. From these sample universities departments that give entrepreneurship course with all its students were taken as sample of the study. Data were collected by using questionnaire and interview from the participants. The result shows that students have participated in extracurricular activities and have a willingness to participate if they get an opportunity. However, students did not participated in business plan competition outside the university, company visit, competition events between students and external stakeholders, seminars and workshops. The major challenges identified are lack of funding available to support the entrepreneurship education, lack of support from the top management and the government and lack of teachers support and encouragement of students practice of entrepreneurship education through extracurricular activities.